Pressurised aerosol deposition in the human lung with and without an "open" spacer device. - Newman, S P (1989)
A radiotracer technique has been used to assess aerosol delivery from a pressurised metered dose inhaler, used both with and without a 10 cm cylindrical spacer attachment (Syncroner), which has an open section in its upper surface. The radionuclide technetium-99m (99mTc) was added to sodium cromoglycate in a canister (Intal inhaler; 1 mg/puff); in vitro studies with a multistage liquid impinger showed that the radiolabel acted as a marker for the presence of drug over a wide range of particle sizes. Ten healthy volunteers were studied after they had inhaled from (1) a metered dose inhaler alone (slow inhaled flow rate, about 25 l/min); (2) metered dose inhaler plus spacer (slow flow rate); and (3) metered dose inhaler plus spacer (fast inhaled flow rate, about 100 l/min). Inhalation was coordinated with firing the spray and was followed by 10 seconds' breath holding. With the metered dose inhaler alone a mean 11.0% (SEM 1.4%) of the dose reached the lungs, compared with significantly higher doses for slow (16.1% (2.2%] and fast (13.3% (1.7%] inhalations through the spacer. The distribution pattern within the lungs was significantly more peripheral after slow inhalation. Oropharyngeal deposition was halved by the spacer. The open spacer should teach patients good coordination and delivers more aerosol to the lungs than a correctly used metered dose inhaler.